Analisis Laju Pernapasan, Gambaran Makroskopis dan Mikroskopis Paru-paru Tikus Wistar yang Diberi Dosis Bertingkat Inhalasi Formalin - Hilkia, Justin (Jurnal Biomedika dan Kesehatan, 2026)
Introduction: Formaldehyde is a colorless organic compound with a pungent odor and is one of the most common indoor air pollutants. Exposure to formaldehyde gas can cause various respiratory issues and can lead to serious health problems. Objective: This study aimed to assess the effects of formalin inhalation on respiratory rate, as well as the macroscopic and microscopic structures of the lungs in Wistar rats. Methods: This experimental study used 24 Wistar rats divided into one control group and three experimental groups, each exposed to different concentrations of formalin vapor for 8 hours per day over a 30-day period. Respiratory rate was analyzed using the chi-square test, while lung weight was analyzed using one-way ANOVA. Results: Although formalin inhalation had no significant effect on the respiratory rate of rats, morphological changes were observed in the lungs, including congestion, hyperemia, and an increase in lung weight and size. Histological examination revealed thickening of the alveolar walls, atelectasis, enlargement of bronchus-associated lymphoid tissue (BALT), as well as fibrosis and necrosis in lung tissue. Conclusion: This study demonstrates that formalin inhalation caused significant lung tissue damage through inflammatory processes that ultimately led to lung injury and pulmonary fibrosis.